A eficiência relativa dos gastos públicos federais em educação superior no Brasil - Silva, Chirley Lima da (2019)
The Federal Universities (UFs), chosen as the object of this study, are primarily maintained with resources passed through the Union and, as public institutions, need to seek efficiency.In this sense, the overall objective of this research is to evaluate the relative efficiency achieved by Brazilian federal universities in allocating public expenditures in 2017. The theoretical approach of the study dealt with higher education, its history, its structure and its functioning. It also addressed the structure of public spending on higher education in Brazil, as well as presented the technique Data Envelopment Analysis (DEA), used to measure the relative efficiency of the UFs. The DEA methodology is a non-parametric technique that involves linear programming to calculate technical efficiency indices. The research was characterized as descriptive, documentary and quantitative. The research universe considered 63 Brazilian federal universities, being thus the study characterized as census. For the application of the DEA, the input factors, which are: Current Cost / Equivalent Student without University Hospital, Equivalent Teacher / Full Time Student and Teacher Qualification Index were collected from the Management Reports of the UFs, and the output factors were the notes of the indicators of the University Ranking Folha 2017, namely:Teaching, Research, Market, Innovation and Internationalization. Results from the DEA analysis using the Frontier Analyst Software revealed that, only 22 of the 63 universities studied were classified as efficient, thus achieving an efficiency score of 1 or 100%. In the ranking of relative efficiency, UFRJ, UnB, UFMG, UFPR and UFCG, among the universities classified as excellent, were considered benchmark, respectively, for 28, 25, 13, 10 and inefficient universities. The results also pointed out that the Market and Innovation indicators are the output factors that most need to be improved in the group of inefficient Decision-making Units in order to achieve relative efficiency in the allocation of public expenditures of the Brazilian federal universities.